2021
DOI: 10.1519/jsc.0000000000003079
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Isometric Squat: Test Reliability, Interlimb Asymmetries, and Relationships With Limb Dominance

Abstract: The aim of the present study was to determine test reliability, establish inter-limb asymmetries and their associations with force production capability on the dominant (D) and non-dominant (ND) limbs during the unilateral isometric squat test. Twenty-eight recreational sport athletes attended a single test session after familiarization and performed three trials on each limb with 140° of hip and knee flexion, to assess peak force (PF), rate of force development (RFD) and impulse at different time intervals. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(44 reference statements)
2
12
1
Order By: Relevance
“…Simply put, if professional players exhibited an asymmetry favouring the right limb (i.e., the right limb scored higher than the left), it was rare for academy players to show similar patterns. This provides further support for the task and population-specific nature of asymmetry, which has been suggested on numerous occasions in previous research [ 9 , 22 , 23 , 28 , 43 ]. In addition, when this is coupled with the large within-group variability of asymmetry (i.e., high SD relative to the mean), we have provided individual asymmetry data for professional ( Figure 1 ) and academy ( Figure 2 ) players.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Simply put, if professional players exhibited an asymmetry favouring the right limb (i.e., the right limb scored higher than the left), it was rare for academy players to show similar patterns. This provides further support for the task and population-specific nature of asymmetry, which has been suggested on numerous occasions in previous research [ 9 , 22 , 23 , 28 , 43 ]. In addition, when this is coupled with the large within-group variability of asymmetry (i.e., high SD relative to the mean), we have provided individual asymmetry data for professional ( Figure 1 ) and academy ( Figure 2 ) players.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to the lower-limb anterior–posterior balance, inter-limb asymmetries in strength should also be monitored for both performance and injury prevention purposes [ 1 , 16 , 22 , 23 , 24 ]. From a performance perspective, inter-limb asymmetry in both knee extensor and knee flexor strength has been reported to be associated with reduced linear ( r = 0.34–0.47) and change in direction speed ( r = 0.39–0.61) ability, while it does not seem to have any detrimental associations on jumping performance [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when considering the unilateral CMJ, despite mean asymmetry being slightly greater than the CV, it must be acknowledged that this metric showed somewhat questionable reliability, with CV values > 13%. This is in part supported by Bishop et al (7) who despite reporting large asymmetry values for rate of force development (22.91%) and impulse (25.46%) during the first 100 milliseconds of a unilateral isometric squat, also showed that CV values were 26 and 32%, respectively. Thus, with suggestions of acceptable variability of < 10% ( 14), practitioners may wish to be cautious of monitoring eccentric impulse during the unilateral CMJ, owing to its heightened variability.…”
Section: Discussionsupporting
confidence: 62%
“…High levels of reliability (ICC: 0.96; TE: 4.6%) have previously been observed for peak force in an isometric mid-thigh pull in youth soccer players 27 . Similarly, unilateral isometric mid-thigh pull 28 and unilateral isometric quarter-squat 29,51 peak force has shown excellent reproducibility (ICC: ≥ 0.94; TE: ≤ 7%). The ICC value for peak force in the present study (right: 0.86 (95% CI 0.61-0.96); left: 0.31 (95% CI -0.33 -0.74)) are lower than those identified for the aforementioned studies; however, the TE appears to be similar (4.4 -6.3%), indicating a comparable level of systematic bias exists compared to previous investigations.…”
Section: Discussionmentioning
confidence: 92%
“…This is likely to be further compounded in participants who are weaker 25 or unfamiliar with a test protocol, such as adolescents. Peak force during isometric mid-thigh pull and quarter-squat tests is a valid indicator of multi-joint lower limb maximal strength 26 , and has consistently been shown to be the most reliable kinetic variable in athletes 24,[27][28][29] ; however, the inter-session consistency of this metric is yet to be established in non-strength-trained adolescent athletes.…”
Section: Introductionmentioning
confidence: 99%